Lost in imagination. Powerful and creative interactions within the safety of a story - Karen Reekmans (European Teacher Education Network, 2023)
This article describes how arts stimulate reading promotion and creative storytelling. Students focus on predictive reading by drawing an announcement to locate a lost thing. The creative process in small groups invites students to exchange ideas about the problem and give impulses for solutions. In addition, it creates opportunities to open a conversation about social issues such as friendship, vulnerability, inclusion and giving opportunities to people nobody seems to notice anymore. Karen Reekmans exemplifies the strategies elaborated in the research projects ArtiCULan, taalCULTuur and Liever lezen using the story "The Lost Thing" written by Shaun Tan